Identification of female specific protein in seabass, Lates calcarifer (Bloch) - Lal, Kuldeep Kumar; Gopalakrishnan, A; Mohindra, Vindhya; James, P S B R (Indian Journal of Fisheries, 2011)
Electrophoretic serum protein profile of female Lates calcarifer reveals appearanceof female specific protein during gonadotropic dependent stages of ovarian growth.The protein is conspicuously absent in the serum of maturing males. The proteinstains positively for carbohydrate, lipids and calcium indicating it to be vitellogenin.The vitellogenin band first appears in fish with maturing ovaries (stage 3) andstain intense and sharp till stage 4. At stage 5 (ripe) the band appears diffused.The protein is lacking in the serum profile of immature (stage 1), restingpreparatory(stage 2) and spent (stage 6) as well as in maturing male fish. Thecorrelative pattern of vitellogenin band with ovarian maturation stages providesevidence of single spawning in L. calcarifer.